Enhancement of IR photoluminescence of β‐FeSi2 nanocrystals by Cu‐doping and study of its mechanism. Issue 11 (25th July 2014) - Maeda, Yoshihito; Tatsumi, Takahide; Kawakubo, Yuki; Noguchi, Yuya; Kobayashi, Hiroyuki; Narumi, Kazumasa; Sakai, Seiji; Pizzini, Sergio; Kissinger, Gudrun
Abstract We have investigated the IR photoluminescence (PL) behavior of Cu‐doped β‐FeSi2 nanocrystals (β‐NCs) embedded in Si layers. The diffusion rate of Cu atom was controlled by annealing. The most appropriate condition brought the largest intensities of both the intrinsic A band emission at 0.803 eV by 214% and the acceptor related C band emission at ∼0.75 eV by 582% in comparison with those of non‐doped β‐NCs. Rutherford backscattering spectrometry (RBS) revealed increase of Cu atoms in the Si layer with β‐NCs with increasing the anneal duration. The C band enhancement surely is originated from increase of a density of state at acceptor levels relating to increase of Cu in β‐lattice. Photocarrier injection PL measurements (PCI‐PL) reveal that the enhancement of the A band emission may be attributed to a controlled migration process of holes with a repeated trap process due to Cu‐doping into the Si phase. This dynamic condition leads to an increase of valence band offset at the β‐NCs/Si heterointerfaces where the migration of holes from the β‐NCs to Si is prevented, so that a radiative recombination rate can be enhanced. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)